PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING DAN INQUIRI BASED LEARNING TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA - Edy Widayat; Suharti Kadar; Novita Febriati (Jurnal Riset Pembelajaran Matematika, 2020)
The aims of this study are: 1). To determine whether there is an effect of Problem Based Learning and Inquiri Based Learning learning models on student learning motivation. 2). To determine whether there is an effect of Problem Based Learning and Inquiri Based Learning learning models on student learning outcomes. 3). To determine whether there is an effect of Problem Based Learning and Inquiri Based Learning learning models on student motivation and learning outcomes. This study was a quasi-experimental study with a pretest-posttest non-equivalent comparison-group design. The data collection instruments included a student learning motivation questionnaire sheet and a student learning outcome test sheet. The test carried out is the one way MANOVA test. The results of the study obtained that there was a significant influence on the learning model of Problem Based Learning and Inquiri Based Learning on student motivation and learning outcomes.